Islamic Microfinance Institutions and Non-Performing Financing (NPF): Challenges and Strategic Response Using Analytic Network Process (ANP) Approach - Muhammad Said; Hartomi Maulana; Rahma Yudi Astuti (MUSLIM HERITAGE, 2025)
Non-Performing Financing (NPF) is financing that does not comply with the initial contract schedule, causing disruption to the cash flow of Islamic microfinance institutions. The average Non-Performing Financing (NPF) of Islamic Microfinance Institutions (MFIs) in 2023 reached 13.09%. The urgency of this study reveals that Islamic MFIs or popularly called as Baitul Maal wa Taamwil (BMT) can be an alternative platform to enhance financial inclusion since they reach out even remote areas. However, NPF is often a problem faced by BMT. The purpose of this study is to analyse the issue of NPF in Islamic MFIs in Indonesia. The study also examines strategies to address issue of NPF in Islamic MFIs in Indonesia. To achieve the research objectives, the method used is through a qualitative approach with Analytic Network Process (ANP) used to be as analysis technique. Primary data sources were obtained through forum group discussions (FGDs) and pair-wise questionnaires and interviews with 10 respondents who are considered experts in related fields. The results of this study indicate that based on the ANP results internal management issue as main problem that causes NPF occur, followed by internal human resource issues, debtor/customer issues and regulatory issues. Main priority of the settlement strategy of NPF include strategy of improving internal management by improving internal human resources, then increasing sharia literacy, and government policy. The study suggests as the issues on internal management is in top rank, the Islamic MFIs should improve internal management elements including enhancing accountability and conducting professional administration.     Abstrak Pembiayaan macet (Non-Performing Financing - NPF) merupakan pembiayaan tidak lancar yang tidak sesuai jadwal kontrak awal, menyebabkan terganggunya arus kas lembaga keuangan mikro Syariah.  NPF pada Lembaga Keuangan Mikro Syariah (LKMS) pada tahun 2023 mencapai 13,09%. Urgensi penelitian ini mengungkapkan bahwa BMT dapat sebagai solusi keuangan inklusif dengan penyebarannya hingga daerah terpencil, yang dapat berinteraksi langsung kepada masyarakat pelaku Usaha Mikro Kecil (UMK). Sehingga NPF kerap menjadi sebuah persoalan yang dihadapi BMT. Dengan demikian tujuan penelitian ini adalah untuk menganalisis isu permasalahan penyebab terjadinya NPF pada LKMS di Indonesia dan menganalisis strategi guna meminimalisir kembali terjadinya NPF pada LKMS di Indonesia. Untuk mencapai tujuan penelitian, pendekatan kualitatif dengan Analytical Network Process (ANP) sebagai teknik analisis digunakan dalam studi ini. Metode ini dapat membantu hasil pengambilan keputusan atau sebuah kebijakan dalam mendapatkan alternatif terbaik diantara isu-isu dan strategi dihasilkan dengan menampilkan urutan prioritasnya. Sumber data primer didapatkan melalui forum group discussion (FGD), kuesioner pairwaise comparison, dan interview dengan 10 responden yang dianggap pakar dalam bidang terkait, yang terbagi dari regulator, akademisi dan praktisi. Hasil penelitian ini prioritas utama isu permasalahan NPF pada BMT terjadi pada manajemen internal, diikuti isu SDM internal, isu debitur/nasabah dan isu regulasi. Sedangkan prioritas utama strategi penyelesaiannya adalah peningkatan manajemen internalnya, diikuti peningkatan SDM internal, lalu peningkatan literasi syariah, dan kebijakan pemerintah. Penelitian ini menunjukkan karena isu manajemen internal berada pada peringkat teratas, LKM Islam harus meningkatkan elemen manajemen internal termasuk meningkatkan akuntabilitas dan melakukan administrasi profesional